Effects of Salbutamol and Furosemide in The Treatment of Transient Tachypnea of Newborn - A Randomized Controlled Trial - Khushdil, Arshad; Ahmed, Zeeshan; Ahmed, Madiha; Nazir, Sajid; Waqar, Talal (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess and compare the effect of Salbutamol and Furosemide therapy in the management of transient tachypnea of newborn.Study Design: Randomized controlled trial (Registered with Clinical Trials.gov: NCT03208894).Place and Duration of Study: Neonatal Intensive Care Unit of Pakistan Emirates Military Hospital Rawalpindi from Oct 2019 to May 2020.Methodology: A total of 100 newborns were included in the study. They were divided into 4 groups. Group-A received nebulized 0.1ml Salbutamol. Group-B was given single intravenous dose of injection Furosemide at the dose of 2mg per kg. Group-C received both IV Furosemide and nebulized Salbutamol. Control group-D received only supportive care.Results: There were 48 male babies and 52 female babies. The average gestational age was 38.8 ± 6.2 weeks and the average birth weight was 2558 ± 620 grams. Administration of both Salbutamol and IV Furosemide together (group-C) showed significant reduction in the mean duration of oxygen dependency compared to control-group (13.40 ± 3.342 vs 83.64 ± 68.546 hours respectively (p